Makna dalam Acara Ritual Adat Galih Tulang sebagai Bentuk Implementasi Hukum Lokal di Sumba Barat Daya - Prety Paskalina Pati Bani; Maria Virginia Jawaina Wotan; Stefanus Don Rade; Mahensa Tapatfeto; Elfege Kotoen Pandong; Lusia Melania Robin; Yohanes Lorensio Mbale; Risto Babtista Kehitos (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The law of engagement is a concept that has existed since ancient times. In the past, engagements often relied on customary law and social norms applicable in a particular society. However, with the increasing development of society and trade, there is a need to have more formal legal rules to regulate agreements and agreements. The term "engagement" refers to the equivalent of the Dutch term "Verbintenis" (Fuadi, 1999: 1). The term contract law includes all provisions in the third book of the Civil Code. The research method uses empirical methods where this method is through observations made by the public. Then it is studied through the customs of the people of Southwest Sumba, especially in kodi regarding the legal relations of engagements that occur with the traditional ritual of removing the bones of ancestors. The data was obtained from an interview with a native Kodi resident named Andreas Ikit Bani, a native descendant of Kodi who often participated in bone dissection rituals. The Galih Tulang event is a traditional ritual carried out by the people of Southwest Sumba to move the bones of their ancestors from old graves to new graves. This ritual is part of a sacred traditional ceremony and is considered important for the people of Southwest Sumba to honor the spirits of their ancestors (Andreas Ikit Bani, 2023). This event has a meaning and purpose that we must know, namely Galing Tulang is a ceremony that must be held to honor our deceased ancestors. The aim is to pay respects to the spirits of deceased ancestors, ask for blessings, and/or give them their proper place in the afterlife.